Technological and Organizational Changes as Determinants of the Skill Bias: Evidence from a Panel of Italian Firms - Mariacristina Piva; Enrico Santarelli; Marco Vivarelli (Max Planck Institute for Research into Economic Systems, 2004)
Recent empirical literature has introduced the "kill Biased Organizational Change" hypothesis, according to which organizational change can be considered as one of the main causes of the skill bias (increase in the number of highly skiled workers) exhibited by manufacturing employment in developed countries. In this paper, a specific branch of the Italian capital goods industry is analyzed, that producing specialized industrial machinery; from the estimation of a transcendental logarithmic firm cost function it turns out that skill upgrading is not a consequence of technological change alone, but is also an effect of the overall reorganization of the firm, which in turn may be linked to technological change.
Keywords: M54; O33; 330; Skill Bias; Organizational Change; Capital goods industry; Reorganisation; Technischer Fortschritt; Qualifikation; Bias; Investitionsgüterindustrie; Kostenfunktion; Schätzung; Italien